Efektivitas Starter Experiment Approach (SEA) Terhadap Kemampuan Berpikir Tingkat Tinggi Peserta Didik Pada Pelajaran Fisika Kelas XI - Joko Purwanto; Daimul Hasanah; Firda Yanuar Syafaat (Jurnal Penelitian Pembelajaran Fisika, 2017)
The aims of this research to know “the efectiveness starter experiment approach (SEA) toward high-order thinking skill of students.” This research is a Quasi Experiment with Nonequivalent Control Group Design. We used XI IPA as population. We used simple random sampling. We used pretest and posttest as instrument to gain/obtain our main data. T-test and Normalized-gain (N-gain) are used to analyze those data.  We obtain score sig.(2-Tailed) = 0,041 < α = 0,05,the percentage increase in students in the high is 8%, moderate is 38%, and low is 54%, experiment class N-gain = 0,33 > control class N-gain = 0,20 These result show that experiment class has more effective than control class. It means starter experiment approach (SEA) proven to effective toward high-order thinking skill of students in physics.